Is bipolar hemiarthroplasty an appropriate type of hip articulation following proximal femoral or total femoral resections for musculoskeletal malignancies? - EROL, BÜLENT; ŞİRİN, EVRİM; KESİMER, MEHMET DENİZ (SPRINGER, 2022)
Background Different approaches are applied for reconstruction in patients with a musculoskeletal malignancy which require a proximal femoral or total femoral resection. We aimed to evaluate the treatment outcomes of patients who underwent a proximal femoral or total femoral resection due to bone and soft tissue tumors and had an endoprosthetic reconstruction by a bipolar hemiarthroplasty type of hip articulation. Methods We retrospectively identified 133 patients who underwent a proximal femoral or total femoral endoprosthetic replacement after resection of a bone or soft tissue malignancy. There were 74 male and 59 female patients, with a mean age of 55.02 +/- 16.92 years (range 11-84 years) and a median follow-up of 24.47 +/- 24.45 months (range 6-164 months). Patient demographics, surgical, and oncological data were recorded. Acetabular wear was measured using the classification proposed by Baker. Functional assessment was performed using the Musculoskeletal Tumor Society (MSTS) functional score. Results There was no statistically significant difference among primary diagnostic groups in terms of gender, prosthesis type, trochanter major resection, local recurrence, complication/revision rate, and MSTS Score (p > 0.05, for each parameter). On the other hand, a statistically significant difference was detected in terms of degree of acetabular erosion among diagnostic groups (p < 0.001); the acetabular erosion rate (AER) was found to be lower in patients with metastatic carcinoma than in patients with a diagnosis of primary bone or soft tissue sarcoma. The univariable analysis revealed that the effect of age, primary diagnosis, localization, follow-up time, and presence and number of distant organ metastasis variables on AER were found to be statistically significant (p = 0.018, p = 0.035, p = 0.002, p = 0.007, p = 0.031, p = 0.040, respectively). Conclusion In patients who undergo a proximal femoral or a total femoral resection due to a musculoskeletal tumor, bipolar hemiarthroplasty is an adequate type of hip articulation method, since it does not affect the revision requirements and functional outcomes of patients with acetabular erosion.
Keywords: Proximal femoral resection; Total femoral resection; Bipolar hemiarthroplasty; Acetabular erosion; BONE-TUMOR; FEMUR; RECONSTRUCTION; ARTHROPLASTY; REPLACEMENT; OSTEOLYSIS; FAILURE; NECK